2021
DOI: 10.33961/jecst.2020.01571
|View full text |Cite
|
Sign up to set email alerts
|

Mo,Cu-doped CeO2 as Anode Material of Solid Oxide Fuel Cells (SOFCs) using Syngas as Fuel

Abstract: Mo,Cu-doped CeO 2 (CMCuO) nanopowders were synthesized by the nitrate-fuel combustion method aiming to improve the electrical and electrochemical properties of its Mo-doped CeO 2 (CMO) parent by the addition of copper. An electrical conductivity of ca. 1.22•10 -2 S cm -1was measured in air at 800 o C for CMCuO, which is nearly 10 times higher than that reported for CMO. This increase was associated with the inclusion of copper into the crystal lattice of ceria and the presence of Cu and Cu 2 O as secondary pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A thin film electrolyte of approximately 10 μm thickness can be prepared on their surface, effectively reducing the internal resistance of the cell and enhancing its output performance. However, Ni-based metal ceramic electrodes also come with certain challenges, especially concerning carbon deposition, sulfur poisoning, and relatively poor redox cycle stability when [ 38,39] Cu-CeO 2 -YSZ Improve the ability to resist sulfur poisoning and carbon accumulation, and have higher electrochemical catalytic activity Cu-doped CeO 2 will decay at low temperature [40] Cu-CeO 2 -Co…”
Section: Fuel Electrodementioning
confidence: 99%
“…A thin film electrolyte of approximately 10 μm thickness can be prepared on their surface, effectively reducing the internal resistance of the cell and enhancing its output performance. However, Ni-based metal ceramic electrodes also come with certain challenges, especially concerning carbon deposition, sulfur poisoning, and relatively poor redox cycle stability when [ 38,39] Cu-CeO 2 -YSZ Improve the ability to resist sulfur poisoning and carbon accumulation, and have higher electrochemical catalytic activity Cu-doped CeO 2 will decay at low temperature [40] Cu-CeO 2 -Co…”
Section: Fuel Electrodementioning
confidence: 99%
“…Recently it has been reported that the addition of molybdenum to CeO 2 (Mo-doped CeO 2 or CMO) confers catalytic activity to the carbon gasification reaction and an increase in the electrical conductivity of CeO 2 (6). Furthermore, it has been reported that the addition of copper nanoparticles to Mo-doped CeO 2 increases its electrical conductivity 10 times (7).…”
Section: Introductionmentioning
confidence: 99%
“…It was also explored that the addition of cobalt to Cu-CeO 2 -YSZ anode cermet can further enhance its catalytic activity, increasing the peak power density of the cell up to 310 mW•cm −2 with H 2 and 370 mW•cm −2 with CO fuel. Further extensive research on Cu-based anodes can be found in the literature [156][157][158].…”
mentioning
confidence: 99%